Imagining the Girl Effect: An Ethnography of Corporate Social Responsibility. Issue 2 (1st June 2022) - Unknown
Abstract : Kathryn Moeller. 2018. The Gender Effect: Capitalism, Feminism, and the Corporate Politics of Development. Oakland, CA. University of California Press.